A Suggested Proposal of a Vocational Program in the Light of the National Professional Standards for Developing Art Education Primary Teachers’ Teaching Skills - Al-Meziraee, Nada Mohammed; Al-Abed, Rehab Mohamed (Journal of Educational and Psychological Sciences, 2021)
The current study aimed at defining the teaching skills required to be developed by art education female teachers in primary schools in light of the national professional standards for art education teachers, then defining the level of teaching performance of art education female teachers in primary schools in light of the targeted skills, And providing a suggested proposal for a professional program in light of the national professional standards to develop the teaching skills targeted for art education female teachers. To achieve the objectives of the study, the descriptive approach was used, and the researcher prepared a questionnaire to determine the teaching skills needed to be developed among art education female teachers, and the study used the observation card as a tool for data collection. It also prepared a suggested vision for a professional program in light of the national professional standards to develop the teaching skills targeted for art education female teachers. After ensuring the validity and reliability of the study tools, they were applied to a random sample of art education female teachers in primary schools in Buraidah, of (18) female teachers. The main results of the study: - The level of teaching performance of art education female teachers in light of the performance indicators related to the national professional standards is weak; as the arithmetic mean of the total scores in the observation card was (1.60) with a standard deviation of (0.198), and the performance level was (53.3%). - One of the standards came with a (high) degree; as the arithmetic mean was from (2.34 to 3.00). - Four of the standards came with a medium degree, as the arithmetic mean was from (1.67 to less than 2.34). - Seven of the standards came with (weak) degree; as the arithmetic mean was from (1.00 to less than 1.67). In light of the previous results, the study recommended to take advantage of the suggested proposal for the professional program prepared by the study in the training of female and male art education teachers during service to develop their specialized teaching skills in light of the national professional standards, and to take advantage of the observation card by the educational supervisors, when doing class visits for art education female teachers; in order to track the teaching performance, and by the female teachers to evaluate their level of performance. And to reconsider the pre-service preparation programs for art education female teachers and developing them to be built in light of the national professional standards for art education teachers.